Single‐cut osteotomy for correction of a complex multiplanar deformity of the radius in a Shetland pony foal. Issue 1 (14th October 2021) - Schweinsberg, Lorenz P.; Ehrle, Anna; Schweinsberg, Uwe; Meehan, Lucy; Noguera Cender, Andrea; Lischer, Christoph J.
Abstract: Objective: To describe the surgical correction of a multiplanar deformity of the radius in a pony using a single‐cut osteotomy. Study design: Case report. Animals: A 9‐week‐old male Shetland pony foal with a bodyweight of 47 kg. Methods: The foal presented with a complex multiplanar deformity of the right radius. A 3‐dimensional model of the bone was created based on computed tomography (CT) imaging. To correct the deformity, the cutting plane for a single‐cut osteotomy was calculated following the mathematical approach described by Sangeorzan et al. After osteotomy, the bone was realigned and stabilized with two 4.5 locking compression plates (LCPs). Results: Recovery from surgery was uneventful, and the foal remained comfortable. A CT exam 15 weeks after surgery revealed that diaphyseal deformities improved substantially in procurvatum (from 8° to 1°), varus (from 27° to 0°), and rotation (30° to 5°). The operated radius was 2.1 cm shorter than the left. Eighteen‐month follow up confirmed a functionally and cosmetically acceptable outcome. Conclusion: The single‐cut osteotomy resulted in the successful correction of a multiplanar equine long‐bone deformity with a favorable outcome in a Shetland pony. Clinical significance: Single‐cut osteotomy is an alternative surgical technique for the correction of complex diaphyseal long‐bone equine deformities. Computed tomography data and the possibility of printing 3D models provides a significant advantage for rehearsing the procedure and for evaluating the correction that was achieved.